PENERAPAN METODE PENUGASAN UNTUK MENINGKATKAN KEMAMPUAN MEMAHAMI PETA PADA SISWA SEKOLAH DASAR - Sutarna, Nana (Jurnal Pendidikan Geografi Gea, 2016)
This research is based on researcher’s concern in the lack of social studies improvement regarding to students’ map understanding. This research aims to improve elementary students’ ability in understanding map. This research uses qualitative approach with classroom action research method. The research model uses cycle model which covers four components: planning, action, observation, and reflection. The research subjects are 35 fourth grade students of SDN 1 Cengal. The instrument uses quistionare, observation sheet, and field data records. Based on the research can be concluded as follow: first, lesson plan in applying assignment method has its own characteristic compared to another lesson plan method. Second, there is learning development process in each cyclus. Assignment method encourages students to be active in learning and stimulates to improve learning process to be better. Third, the average score in the cyclus I is 70,07, the average score in the cyclus II is 73,83 and the average score in the cyclus III is 82,00. From the explaination above, can be concluded that there is the development in each cyclus which means that assignment method can improve the map understanding ability in elementary students. Keywords: learning, map, assignment method, cycle.